(untitled) (Global Journal of Human-Social Science, 2026)
In this research work the 101 verses composed by Abirami Bhattar of Abirami Anthati has been taken up to explore the possibility of picturizing the concept of bakthi enunciated by Bhattar. Care has been taken not to compare with other works thereby it enables the reader to fully engage themselves and revel in the bliss of bakthi (devotion) as contemplated by Bhattar though to some extent the Bakthi Movement of India, definition of bakthi and a brief history of Bhattar bas been discussed in the beginning of the research work. As a whole this research endeavor would open up avenues for greater discussion on the ancient concept of bakthi greatly underlie in the Indian Philosophy.